Genetic variants in LGALS3 are related to lower galectin-3 serum levels and clinical outcomes in systemic sclerosis patients: A case-control study - Eudes Gustavo Constantino Cunha; Camilla Albertina Dantas de Lima; Kamila de Melo Vilar; Marcelo Francisco de Nóbrega; Anderson Rodrigues de Almeida; Michelly Cristiny Pereira; Andréa Tavares Dantas; Rafaela Silva Guimarães Gonçalves; Moacyr Jesus Barreto de Melo Rêgo; Angela Luzia Branco Pinto Duarte; Maira Galdino da Rocha Pitta (Taylor & Francis Group, 2021)
Introduction Systemic sclerosis (SSc) is a rare complex disease characterized by vascular damage, autoimmunity, and extensive skin and internal organs fibrosis. Galectin-3 (Gal-3) is encoded by gene LGALS3 (Lectin, Galactoside-Binding, Soluble, 3; 14q22.3) and it has been reported to play a central role in self-tolerance, inflammation, and fibrosis. Objective To investigate associations among LGALS3 single nucleotide polymorphisms (SNPs) and serum levels Gal-3 and SSc susceptibility and their clinical features. Methods A case-control study with 88 patients and 151 matched controls was performed. LGALS3 variants were analyzed by the TaqMan real-time polymerase chain reaction (PCR) system whereas Gal-3 serum levels were measured by sandwich enzyme linked immunosorbent assay (ELISA). Associations among genotypes, clinical features, and Gal-3 levels were performed by univariable and multivariable analysis through statistical packages. Results The LGALS3 rs4652 A/C genotype was more frequent in SSc patients than controls according to overdominant model [OR 1.89 (CI 95% 1.01 − 3.52); p = .046]. Also, LGALS3 rs4652 C/C polymorphic genotype was associated with lower patient Gal-3 levels (p = .03) and control group (p = 0.005), as noted by generalized linear model (GLM). The LGALS3 rs1009977 G/T controls showed higher Gal-3 levels than wild-type and polymorphic genotypes (p = .03); however, in SSc patients, no difference was found. None of the LGALS3 SNPs or Gal-3 levels was associated with clinical manifestations in SSc patients. Considering only the SSc group, GLM analysis pointed LGALS3 rs4652 and rs2075601, pulmonary arterial hypertension (PAH), myopathy, and health assessment questionnaire (HAQ) and scleroderma health assessment questionnaire (SHAQ) as important predictors for Gal-3 levels. Conclusion The LGALS3 rs4652 A/C was more frequent in SSc patients and related to lower Gal-3 levels. These findings were corroborated through a GLM to estimate Gal-3 values. Also, by model equations, Gal-3 levels may be predicted by HAQ, SHAQ, PAH, myopathy, and LGALS3 rs4652 and rs2075601 factors. In these ways, we suggest that galectins may be promising biomarkers to identify susceptibility to SSc as well as to identify HAQ, SHAQ, PAH, and myopathy outcomes.